2014
DOI: 10.1007/s11046-014-9765-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ras-Mediated Signaling in Aspergillus fumigatus

Abstract: Pathogenic fungi employ numerous mechanisms to flourish in the stressful environment encountered within their mammalian hosts. Central to this arsenal for filamentous fungi is invasive growth within the host microenvironment, mediated by establishment and maintenance of polarized hyphal morphogenesis. In Aspergillus fumigatus, the RasA signal transduction pathway has emerged as a significant regulator of hyphal morphogenesis and virulence, among other processes. The factors contributing to the regulation of Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
(55 reference statements)
0
20
1
Order By: Relevance
“…Ras1p plays an important role in regulating pseudohyphal growth by activating a MAPK cascade and the cAMP/PKA cascade (677). Similar roles for Ras homologs have also been reported for the filamentous morphogenesis of other fungi where the rasA (ras1) gene products regulate events in germination, including mitosis, as well as in completion of the asexual developmental cycle and polarized growth of hyphae (676,(678)(679)(680). Other roles for Ras1 homologs include activating cAMP synthesis in C. albicans, causing the yeast-to-hypha transition (677), high-temperature growth, and virulence in C. neoformans (681), mating and haploid filamentous growth (678,679) and the pheromone response in U. maydis, where the expression of a dominant-active allele of ras1 (Ras1 Q67L ) induced the transcription of the pheromone precursor gene mfa1 with no other apparent phenotypic alteration (682).…”
Section: Ras-gtpasesmentioning
confidence: 57%
See 1 more Smart Citation
“…Ras1p plays an important role in regulating pseudohyphal growth by activating a MAPK cascade and the cAMP/PKA cascade (677). Similar roles for Ras homologs have also been reported for the filamentous morphogenesis of other fungi where the rasA (ras1) gene products regulate events in germination, including mitosis, as well as in completion of the asexual developmental cycle and polarized growth of hyphae (676,(678)(679)(680). Other roles for Ras1 homologs include activating cAMP synthesis in C. albicans, causing the yeast-to-hypha transition (677), high-temperature growth, and virulence in C. neoformans (681), mating and haploid filamentous growth (678,679) and the pheromone response in U. maydis, where the expression of a dominant-active allele of ras1 (Ras1 Q67L ) induced the transcription of the pheromone precursor gene mfa1 with no other apparent phenotypic alteration (682).…”
Section: Ras-gtpasesmentioning
confidence: 57%
“…Members of the Ras family of GTPase proteins are involved in morphogenesis and virulence in many organisms, including several species of pathogenic fungi (676). S. cerevisiae contains two highly similar Ras homologs, RAS1 (TR_120150, TA_301172, and TV_60928) and RAS2 (TR_110960, TA_323248, and TV_54919), and both have redundant cellular functions.…”
Section: Ras-gtpasesmentioning
confidence: 99%
“…After post-translational modification is complete, RasA primarily localizes to the A. fumigatus plasma membrane (PM) (Fortwendel et al, 2012). However, mutation of either the highly conserved cysteine residues required for palmitoylation or of the CAAX-box cysteine required for prenylation, leads to mislocalization of RasA to endo-membranes (EM) and to the cytoplasm, respectively (Fortwendel et al, 2012; Norton and Fortwendel, 2014). Further study of these mutants revealed that PM-localized RasA regulates the major signaling programs for hyphal morphogenesis, cell wall integrity, asexual development and virulence (Fortwendel et al, 2012).…”
Section: Human Pathogenic Fungi: Aspergillus Fumigatus Mucor Racementioning
confidence: 99%
“…Further study of these mutants revealed that PM-localized RasA regulates the major signaling programs for hyphal morphogenesis, cell wall integrity, asexual development and virulence (Fortwendel et al, 2012). However, EM-localized RasA supports hyphal growth to a greater extent than cytoplasmic RasA, suggesting that RasA may retain the ability to engage signaling partners from the EM (Fortwendel et al, 2012; Norton and Fortwendel, 2014). These findings require further investigation, but may suggest that filamentous fungal Ras proteins, like those of their yeast and human counterparts, are able to use multiple membranes as signaling platforms to achieve distinct outcomes.…”
Section: Human Pathogenic Fungi: Aspergillus Fumigatus Mucor Racementioning
confidence: 99%
“…The Ras signaling pathway provides a link between environmental cues and changes in cell physiology in a variety of species [5]. The manuscript by Norton and Fortwendel examines how post-translational modifications influence spatiotemporal regulation of Ras proteins in A. fumigatus and reveals the importance of this pathway to polarized invasive growth [6]. During infection, A. fumigatus must also adapt to the oxygen-limited environment of host tissues [7].…”
Section: Fungal Stress Responsementioning
confidence: 99%